Development of an in vivo swine model of biliary dilatation‐based direct peroral cholangioscopy. Issue 5 (5th April 2016) - Park, Jin‐Seok; Jeong, Seok; Kwon, Chang‐Il; Jong Choi, Hyun; Hee Koh, Dong; Hee Cho, Jae; Jin Hyun, Jong; Moon, Jong‐Ho; Lee, Don Haeng
Abstract : Background and Aim: A reproducible in vivo swine model of bile duct dilation (BDD) was recently established and reported for preclinical testing of newly developed biliary devices or endoscopic techniques. The aim of the present study was to develop a more advanced large animal model in which it is possible to direct examination of the biliary tree. Methods: Six mini pigs were prepared for the study. BDD models were first made by closure of the Vater's ampulla in all swine. Then endoscopic papillary balloon dilation (EPBD) was done in the animals. Feasibility of single‐operator peroral cholangioscopy without assistance of accessories was evaluated using an ultra‐slim upper endoscope in the animals. Results: EPBD could be implemented using a dilation balloon catheter (10~13.5 mm) in all BDD models (6/6, 100%). Success rate of freehand direct insertion of an ultra‐slim endoscope into the common bile duct was 100% (6/6), and access to the common hepatic duct with examination was possible using direct peroral cholangioscopy in five animals (5/6, 83.3%). None of the animals died. In the cholangioscopic examination, a bile duct polyp and a benign biliary stricture occurred naturally, respectively, in two of the six swine. Conclusion: An in vivo swine model of biliary dilatation‐based direct peroral cholangioscopy was established. This novel animal model may be useful for preclinical research of new materials or devices because direct visualization of the biliary tree is feasible.